(untitled) (Research, Society and Development, 2022)
The objective of this research was to evaluate the production of enzymes by bacteria that promote plant growth and the effect of inoculation of these bacteria on the decomposition of organic residues and solubilization of phosphorus. In the first experiment, the production of amylase and cellulase enzymes by eight bacterial strains were analyzed. These tests were carried out in a culture medium and the presence of enzymes was verified by halo formation. The second experiment was installed in adapted respirometers, containing soil, plant residues of pigeon pea (Cajanus cajan), brachiaria (Brachiaria decumbens) and control without addition of residue and addition of natural phosphate from Bayóvar, followed or not by inoculation with bacterial strains. . Assessments of C-CO2 evolution were performed weekly for a period of 42 days. After the evolution period of C-CO2 evaluation, the soil of the incubation chambers was used to analyze the phosphorus concentration. As a result, it was verified that UNIFENAS 100-24 was potentially capable of producing amylase and cellulose. This strain promoted greater release of C-CO2, however, no greater release of phosphorus was observed. Inoculation with the UNIFENAS 100-24 strain can promote greater decomposition of organic residues, favoring nutrient cycling and improving soil quality.